DIASTOLIC DYSFUNCTION IN PATIENTS OF TYPE 2 DIABETES MELLITUS - MAYURESH DIXIT; P.Z. WADIA; R.H.DESHPANDE; SADHANA DESHPANDE-DIXIT (International Journal of Pharma and Bio Sciences, 2016)
This study was aimed to know cardiac dysfunction in patient type ll diabetes mellitus. 100 patients of type ll diabetes mellitus of more than 5 years duration attending medical OPD and admitted in New Civil Hospital Surat were taken for study. ECG and 2D ECHO with doppler was done to know the cardiac dysfunction and other routine investigations related to the subject were done. Mean age of diabetic patients was 57.17 years, Ratio of male to female was 1.17:1,As the age of diabetic patients increases, LV diastolic function decreases. Mean EF% was found lower in 60-75 years group (47.39%) as compared to 51.66%-of 40-49 years age group. Mean Ve/Va was found lower in 60-75 years group (0.84) as compared to 0.88 of 40-59 years age group. As BMI increases, LV diastolic dysfunction increases. It is concluded that left ventricular dysfunction was present in significant proportion of asymptomatic diabetic patients.